SURVEILLANCE AND PREVENTION OF RADICALIZATION AMONG RETIRED INDONESIAN MIGRANT WORKERS: A HOLISTIC APPROACH TO NATIONAL SECURITY IN NORTH SULAWESI - Pinta Simamora; Grenaldo Ginting; Pingkan Kaunang; Joni Kutu' Kampilong; Angereine Pinontoan; Hanzel Mamuaya (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Indonesia's labor migration creates a huge amount of remittances, but the recall (PMI Purna) is vulnerable. In North Sulawesi, repatriated workers are economically marginalized, face psychosocial loads, geopolitical vulnerabilities, and risk becoming radicalized. This study analyzes the influences of vulnerability, institutional lacunae, and policy options on preventative supervision. A mixed method sequenced explanatory study was adopted, combining normative–normative–juridical analysis and fieldwork in Manado, Sangihe, Talaud, and Bitung. Consultations with stakeholders, focus group discussions, 100 interviews with returnees, and observations, were used for data collection. Thematic analysis identified patterns of deprivation, stigma and institutional fragmentation from repetition across the different case studies. Findings show that there is a regulatory micronucleus between Law No. 18/2017 (labor protection) and Law No. 5/2018 (counter-terrorism), placing ordinary returnees in a